Cuidado educativo : relações e possibilidades de uma práxis transformadora no ensino superior - Borges, Rosália Figueiró (2015)
This study is a qualitative approach - linked to the line of research Individual Education and the Graduate Program in Education Pontifical Catholic University of Rio Grande do Sul (PUCRS). Has as objective to know the relationship between the care process and the educational process in the teaching practice of higher education in the humanities and exact areas in order to draw attention to a more holistic and human Education framework. The research covered the proposition to understand the relationship between the process of care, teaching practice, teaching and higher education in the humanities and exact areas from the perspective of university teaching. Teachers were interviewed in order to interpret the phenomena based on the objective. Data were collected in three stages: invitation, awareness, personal perception of teaching through semi-structured interviews, in a private university in São Leopoldo / RS For the analysis of the individual interviews data, we opted for the analysis of content proposed by Bardin (2008), in the pre-analysis, material exploration, treatment and interpretation of the results, in which appeared the four categories of this study: 1) Care and education: a matter of understanding, 2) Training and Self-training : care as the foundation; 3) classroom: caring in action 4) Watch as the basis of university education. The core of educational practice is not restricted to a classroom, but the care environment that can be brought about so that the students to venture in knowledge. The teacher uses a combination of multiple knowledge between teaching, reality and caring. The "Caregiver Educator", can be a symbol of transformation, effective actions and possibilities of a process that should be permanent: the integration of self and responsibility to one another and to society. The opportunity to experience the art of care in higher education can be generator of an office and a stronger teaching practice of possibilities and meanings enriched between "being", "do" and "feel". The thesis established the relationship between human care, teaching practice and higher education, it was revealed that the care is intrinsically associated with the teaching knowledge subjectivizing and a unique know-how that can provide a context of holistic education. There is a concern, a zeal that would correspond to an educational care, with direct action recognition of the student.